Perception of Work Locus Control Among Nurses in Shree Birendra Hospital, Chhauni, Kathmandu, Nepal - Bajracharya, M (Medical Journal of Shree Birendra Hospital, 2005)
Perception of Work Locus Control Among Nurses in Shree Birendra Hospital, Chhauni, Kathmandu, Nepal